Computational systems‐biology approaches for modeling gene networks driving epithelial–mesenchymal transitions. Issue 2 (9th June 2021) - Katebi, Ataur; Ramirez, Daniel; Lu, Mingyang
Abstract: Epithelial–mesenchymal transition (EMT) is an important biological process through which epithelial cells undergo phenotypic transitions to mesenchymal cells by losing cell–cell adhesion and gaining migratory properties that cells use in embryogenesis, wound healing, and cancer metastasis. An important research topic is to identify the underlying gene regulatory networks (GRNs) governing the decision making of EMT and develop predictive models based on the GRNs. The advent of recent genomic technology, such as single‐cell RNA sequencing, has opened new opportunities to improve our understanding about the dynamical controls of EMT. In this article, we review three major types of computational and mathematical approaches and methods for inferring and modeling GRNs driving EMT. We emphasize (1) the bottom‐up approaches, where GRNs are constructed through literature search; (2) the top‐down approaches, where GRNs are derived from genome‐wide sequencing data; (3) the combined top‐down and bottom‐up approaches, where EMT GRNs are constructed and simulated by integrating bioinformatics and mathematical modeling. We discuss the methodologies and applications of each approach and the available resources for these studies.